Giant malignant fibrous histiocytoma of the face: case report of microsurgical repair using a transverse rectus abdominis myocutaneous flap - Rui Antonio Aquino De Azevedo; Breno Ricelly Ávila Pinheiro; Raina Caterina Coelho Arrais; Bruno Fabrício Ávila Pinheiro (Revista Brasileira de Cirurgia Plástica)
Introduction: The resection of invasive tumors of the head and neck can result in extensive and complex defects requiring immediate repair. One repair option is the transfer of a transverse rectus abdominis myocutaneous (TRAM) flap pedicled on deep inferior epigastric vessels using vascular microsurgery. This study aimed to register a procedure used in the microsurgical treatment of giant malignant fibrous histiocytoma of the face using a TRAM flap. Case Report: A male patient sought medical care for a giant tumoral lesion in the right hemiface. Computed tomography of the skull revealed a voluminous expansive process of vegetating aspect with poorly defined borders. The excision of the tumor affected the right masseter and temporalis muscles, parotid gland, and right orbital and malar bones. Subsequently, microsurgical withdrawal of the TRAM flap was performed with the deep inferior epigastric artery through a surgical incision in the hypogastric area. Dissection of the facial artery and vein under microscopy and venous and arterial anastomoses followed. The flap was intact with good perfusion and no signs of infection. Conclusions: Microsurgical facial reconstruction allows head and neck surgeons to resect large tumors.